The teacher's role of hour-activity in early childhood education: a historical analysis (Research, Society and Development, 2020)
This all seeks to understand a historical need of the activity of the hour-activity teacher. For this, a documentary research was carried out, in which we analyzed the historical process of the laws that regulate funm fun'o of the teacher of the hour activity in the Children's Education. Or work justifies bringing reflections on or teaching work, to organize and the purpose of the school to ensure the quality of teaching. Results and argues that, according to the promulgation of the Federal Constitution-the Of 1988 and law of guidelines and bases (Law 9394/96), whose character of democratization of teaching and valorization, together with a professional mourning, in agreement with the union movements, resulted in the construction of Law 11,738 of July 16, 2008, at the federal level, which stabbed the teachers the Hour-Activity, that is, 1/3 gives workload two teachers start to elaborate the planning of activities, assistance to parents, students, realization of resources, organization of materials, formacao and studies. Not in the meantime, to ensure that it is important for teachers and, inconsequence, a qualification of the student it was necessary for States and Municipalities to reorganize their routine policies and hiring, used funds to meet this demand. Thus, organize as disciplines for all teachers to perform or moment gives hourly activity, because municipal schools began to offer offices such as: English, Educação-Física, Art, among others and how institutions of Children's Education needed to organize offices with teachers, known as teachers of the hour-activity / regent II / regent B, which acts once a week to subdue the load time. In fact, it is considered that the history of the teaching act revealed the professional struggle of the Magisterium to guarantee and maintain the right of the hour-activity, coming from the mobilization of education workers, therefore, it demonstrates that through the history of the past, the present and that it still produces new stories in the future, which has in mind, the need for hour-activity as a condi'o and valorise of teaching work and a question of valuing this professional who seeks to guarantee or derito of the education of qualidad. The research also reveals the counter-activity between the conquest of the hour-activity right, as ruptures and brings the continuity of the struggles for the recognition and appreciation of these professionals of the Children's Education.